IMUNISASI: FAKTOR-FAKTOR ORANG TUA MENGAMBIL KEPUTUSAN PEMBERIAN IMUNISASI - Ayuni Nur Rachmah; Annisa Nurida; Uning Marlina (PROCEEDING UMSURABAYA, 2023)
Every year more than 1.4 million children worldwide die from diseases that can be prevented by immunization. An estimated 1.7 million deaths or 5% occur in children in Indonesia are due to PD3I. Immunization is the primary prevention against infectious diseases. The preparation of this literature review aims to determine what factors influence the decision of parents to immunize their children because in Indonesia itself there is still a low immunization coverage.Â Search and collection of literature studies using relevant keywords ("factors affecting immunization" or "completeness of immunization factors" or "reasons for immunization in children" or "factors that influence immunization) that are searched through online databases such as google schoolar and PubMed and relevant journal website addresses. The selected journals are journals in the period 2010 to 2020 with a minimum publication category indexed by Scopus and SINTA 4.Â from 15 relevant journals, family knowledge and support are the factors most often cited as factors influencing immunization decisions. There are 2 factors that influence a mother's decision to immunize her child, namely internal factors, which are within the scope of the individual (age, education, work, knowledge, family support, perception, and reminding) and external, are external factors (information received both from counseling health workers and from the role of community leaders, distance of the house from the location of services, composition of vaccines, and the availability of vaccines)Keywords: immunization, influencing factors, decisions, parents